IMPROVING THE EFFECTIVENESS OF SPIRITUAL AND EDUCATIONAL TEACHING AT THE INSTITUTE: PROBLEMS AND SOLUTIONS (Modern education and development, 2025)
Today, universities strive to ensure the normal functioning of the educational process, the qualitative achievement of educational results that meet the state standard, and the necessary level of motivation, health, and development of students. Educational institutions are trying to switch from a functioning mode to a development mode, purposefully engaging in innovative work. The purpose of this article is to create a control system as one of the ways to improve the effectiveness of education quality management.